2017
DOI: 10.1186/s12916-017-0825-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between the day of the week of milestones in the care pathway of patients with hip fracture and 30-day mortality: findings from a prospective national registry – The National Hip Fracture Database of England and Wales

Abstract: BackgroundRecent publications indicate increased mortality in patients admitted to hospital at the weekend, but these findings may be subject to inadequate adjustment for case-mix and the complexities of resource provision. Hip fractures generally occur in a frail comorbid population with a consistent diagnosis precipitating admission as an emergency. We therefore aimed to examine the association between the day of the week of milestones in the care pathway and 30-day mortality in this population.MethodsUsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 25 publications
2
54
1
1
Order By: Relevance
“…However, not all studies showed increased in -hospital mortality in patients admitted to the hospital at weekends. 40, 41 In our study, hospital admissions at weekends, as well as those on other nonworking days (public holidays), were significant predictors of in -hospital mortality. We also observed that the number of deaths was higher on Wednesdays, Thursdays, and Fridays than on Mondays.…”
Section: What's New?mentioning
confidence: 47%
“…However, not all studies showed increased in -hospital mortality in patients admitted to the hospital at weekends. 40, 41 In our study, hospital admissions at weekends, as well as those on other nonworking days (public holidays), were significant predictors of in -hospital mortality. We also observed that the number of deaths was higher on Wednesdays, Thursdays, and Fridays than on Mondays.…”
Section: What's New?mentioning
confidence: 47%
“…Trochanteric fractures represent between one third and one half of hip fractures. 1,4,5 There is controversy regarding treatment. Some authorities recommend an extramedullary device (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although most patients (> 75%) were admitted to hospital within 6 hours of presentation at the emergency department (mean 7.58 h [SD 11.87]), only 14 174 (33.5%) received surgery within the recommended time frame (24 h) ( Figure 1). 1,47,48 The proportion of patients with hip fracture is also reported by their time of presentation, admission and surgery in Appendix 2, available at www.cmaj.ca/lookup/suppl/doi:10.1503/cmaj.170830/-/ DC1. Whereas 5837 patients (13.8%) arrived overnight, only 441 patients (1.0%) received surgery during this time.…”
mentioning
confidence: 99%
“…Two-thirds (66%) of the participants did not receive surgery within the safe time frame (24 h). 1,47,48 Variation within Ontario's public health care system warrants performance improvement at the hospital level.Variation in wait times was attributable to treatment at different hospitals, as opposed to treatment by different phys icians. As such, initiatives for quality improvement may target hospitallevel processes preferentially rather than individual physician practices.…”
mentioning
confidence: 99%